Klasifikasi Wajah Kambing Peranakan Ettawa (PE) Jantan Berbasis Perseptron - Chamim, Anna Nur Nazilah; Soesanto, Adhi; Soesanti, Indah (Semesta Teknika, 2014)
Goat Peranakan Ettawa ( PE ) is a kind of superior goat derived from goat crosses, between Ettawa (Jamnapari ) from India and Kambing Kacang (Bean Goat) from Java. A factor to determine quality of goat PE is itâs face. More than 30 cm ears length and the head color is black represents good quality. More better the quality of goat face, means higher selling price. In this study, male goat face is classified into class good quality, less good, and not good at data such as photo / image In the market, classification done by visual observation, so many farmers have difficulty in classifying the face of a goat. For that purpose, a system is needed that capable for classifying a goat face to facilitate farmers in classifying.This classification system uses Perceptron Method, is a method of guided learning using characteristic as input those are ears length, black value and brown face value. Images are used as training images as much as 9 images, and test images are 20 images. This system could classificating PE goat face with success rate of 95% and 1 error from 20 testing images. Error occured because the background was detected as black and image taking that not precise.